Identifying components required for OMP biogenesis as novel targets for antiinfective drugs. Issue 7 (3rd October 2017) - Weirich, Johanna; Bräutigam, Cornelia; Mühlenkamp, Melanie; Franz-Wachtel, Mirita; Macek, Boris; Meuskens, Ina; Skurnik, Mikael; Leskinen, Katarzyna; Bohn, Erwin; Autenrieth, Ingo; Schütz, Monika
ABSTRACT: The emergence of multiresistant Gram-negative bacteria requires new therapies for combating bacterial infections. Targeting the biogenesis of virulence factors could be an alternative strategy instead of killing bacteria with antibiotics. The outer membrane (OM) of Gram-negative bacteria acts as a physical barrier. At the same time it facilitates the exchange of molecules and harbors a multitude of proteins associated with virulence. In order to insert proteins into the OM, an essential oligomeric membrane-associated protein complex, the ß-barrel assembly machinery (BAM) is required. Being essential for the biogenesis of outer membrane proteins (OMPs) the BAM and also periplasmic chaperones may serve as attractive targets to develop novel antiinfective agents. Herein, we aimed to elucidate which proteins belonging to the OMP biogenesis machinery have the most important function in granting bacterial fitness, OM barrier function, facilitating biogenesis of dedicated virulence factors and determination of overall virulence. To this end we used the enteropathogen Yersinia enterocolitica as a model system. We individually knocked out all non-essential components of the BAM (BamB, C and E) as well as the periplasmic chaperones DegP, SurA and Skp. In summary, we found that the most profound phenotypes were produced by the loss of BamB or SurA with both knockouts resulting in significant attenuation or even avirulence of Ye in a mouse infection model. Thus, we assume that both BamB and SurA are promising targets for the development of new antiinfective drugs in the future.